Učitelský sbor české základní školy - Petr Urbánek (Orbis Scholae, 2019)
Most studies about teachers and the teaching profession in the Czech Republic and elsewhere focus on the teacher as an individual. Interest is for instance on their professional characteristics, teacher training programmes, and working conditions. These analyses hardly reflect the fact that the teacher is a part of the staff, tied with colleagues and the professional environment both organizationally and ideologically. This study is a review of published knowledge about the Czech basic school teaching staff. The paradoxes of the teaching profession and the school as an organization suggest that the basic school teaching staff are a rather distinct professional society. The subject of the study is the teaching staff characteristics, the structure, personnel turnover and the teaching staff social climate. Research results differentiate between the manifested climate and the causes of the climate. More specifically, similar climates are the result of different and sometimes unique causes. There are key factors which this research identifies as crucial for the openness of the teaching staff climate: school leadership style, and the personnel constellation of the staff. Beneficial for the climate is a balance between personnel stability and a reasonable rate of personnel turnover.